Which Nationalism for the Anthropocene? A Comparative Study of Exemplary Green Nation-States - Conversi, Daniele; Posocco, Lorenzo (Frontiers in Political Science, 2022)
This article poses, and attempts to answer, two correlated questions: (1) Is nationalism, the dominant ideology in our world of nation-states, compatible with the struggle to halt or minimize climate change and related environmental catastrophes? and (2) Which form(s) of government, whether or not informed by nationalist ideology, could better address the most serious threat to human life that currently appears on the horizon? This article puts forward the claim that while the former question has only recently begun to be explored in a few essays and articles devoted to analyzing the linkages between nationalism and climate change, the latter remains unexplored. Attempting to fill this gap, we investigate case studies of exemplary nation-states that periodically scored the highest in the Environmental Performance Index (EPI) and the Climate Change Performance Index (CCPI): Scandinavian countries (Norway, Sweden, Denmark), Switzerland, and Germany. Their cities received environmental awards (i.e., the European Green Capital Award) and registered the highest levels in terms of citizen satisfaction. The goal is to identify factors and (pre)conditions that make forms of “green nationalism” possible.